Strategies for Overcoming Teachers’ Resistance to Change in 21st Century Education: Teachers’ Perspectives - Suci Rahmadani; Rima Nurdiani Harahap; Sri Bina Br Sembiring (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Resistance to change (RTC) is a significant challenge in implementing educational reforms, particularly in the 21st century. This study explores strategies to overcome RTC among educators, using a qualitative approach involving 20 teachers from diverse backgrounds. Data collected through open-ended questions and a Likert scale reveal that Facilitation and Support (85%) and Negotiation and Agreement (90%) are the most effective strategies, highlighting the importance of training, resource allocation, and incentives in fostering adaptability. Participation and Involvement (75%) also proves effective by enhancing teacher commitment through collaborative decision-making. In contrast, Manipulation and Co-optation and authority-driven strategies are viewed as less sustainable, with respondents expressing concerns over their long-term impact. Challenges such as frequent curriculum changes, limited technological proficiency, and unclear communication exacerbate RTC. This study emphasizes the need for practical strategies like direct support, collaboration, and motivational incentives to address resistance effectively. The findings extend Kotter and Schlesinger’s framework by contextualizing it within educational settings and highlight the interplay between external pressures for reform and internal resistance mechanisms. By aligning resources, fostering collaboration, and incentivizing participation, schools can navigate the complexities of change and reduce resistance among educators.